(3Pjd JGQjN HZOGOs - (3CHi YHO Gddg eMeO Hf SYjO Hf eMeO Hf GdOjHTis; (3CMeO Hf Ydj Hf KGHJ GdHZOGOj, CHhHcQ,GdNWjH GdHZOGOj,J (B463 (3g` s
(3ChdgG (B:s
(3JQLeI (B: (3CMeO Hf ESeGYjd Hf eMeO Hf YHO GdhGMO Hf RQjb s
(3BNQgG (B:s
(3Edi BNQ MQha GdMGA s
(3GdeLdO GdKGfi ef fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B154 s
Keywords: (3GdJGQjNs